FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN TERHADAP PENJUALAN SEPEDA MOTOR YAMAHA PADA CV. MAHKOTA MOTOR PEKANBARU - Sahroini, Desi; Syabrus, Hardisem; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTCV. Mahkota Motor Pekanbaru is one company engaged in the distribution and marketing of two-wheelers under the brand Yamaha . The diversity of price and the type presented by the company in order to compete in meeting consumer demand for motorcycles and make a decision to buy a motorcycle . To attract the attention of consumers , companies provide after sales service as genuine Yamaha parts . The company also provides convenience in terms of payment of the products sold by way of cash and credit. The purpose of this study was to determine and analyze whether the factors that affect customer satisfaction with the sales of Yamaha motorcycles in CV. Mahkota Motor Pekanbaru . The sample used in this study are all consumers CV. Mahkota Motor which still have dependents with as many as 60 companies . Data collection techniques using observation , documentation , and questionnaires . Analysis using quantitative descriptive method and linear regression. The results showed that the partial product and service quality significantly affect sales of Yamaha motorcycles in CV . Motor crown with a value of F = 3.349 and F table = 2.9113 so that the larger F value of F table and a significance value of F is 0.790 greater than the value of α of 0.05 . Keywords : Quality of Products , Services , Sales